The Tools of Policy Formulation: Actors, Capacities, Venues and Effects - Andrew J. Jordan (New Horizons in Public Policy series, 2015)
Policy analysts are accustomed to thinking in terms of tools and instruments. Yet an authoritative examination of the tools which have been developed to formulate new policies is missing. This book is the first of its kind to distinguish the defining characteristics of the main policy formulation tools, and offer a fresh way of understanding how, why and by whom they are selected, as well as the effects they produce in practice. CONTENTS Preface Acknowledgements PART I INTRODUCTION 1. The Tools of Policy Formulation: An Introduction John R. Turnpenny, Andy J. Jordan, David Benson and Tim Rayner PART II TOOLS OF POLICY FORMULATION 2. Participatory Assessment: Tools for Empowering, Learning and Legitimating? Matthijs Hisschemöller and Eefje Cuppen 3. Scenarios: Tools for Coping with Complexity and Future Uncertainty Marta Pérez-Soba and Rob Maas 4. Indicators: Tools for Informing, Monitoring or Controlling? Markku Lehtonen 5. Computerized Models: Tools for Assessing the Future of Complex Systems? Martin K. Van Ittersum and Barbara Sterk 6. Multi-Criteria Analysis: A Tool for Going Beyond Monetization? Catherine D. Gamper and Catrinel Turcanu 7. Cost-Benefit Analysis: A Tool That is Both Useful and Influential? Giles Atkinson PART III ACTORS, CAPACITIES, VENUES AND EFFECTS 8. Policy Formulation, Policy Advice and Policy Appraisal: The Distribution of Analytical Tools Michael Howlett, Seck L. Tan, Andrea Migone, Adam Wellstead and Bryan Evans 9. The Use of Policy Formulation Tools in the Venue of Policy Appraisal: Patterns and Underlying Motivations John R. Turnpenny, Andrew J. Jordan, Camilla Adelle, Stephan Bartke, Thomas Bournaris, Petrus Kautto, Hanna Kuittinen, Lars Ege Larsen, Christina Moulogianni, Sanna-Riikka Saarela and Sabine Weiland 10. Policy Formulation Tool Use in Emerging Policy Spheres: A Developing Country Perspective Sachin Warghade 11. The Effects of Targets and Indicators on Policy Formulation: Narrowing Down, Crowding Out and Locking In Christina Boswell, Steve Yearley, Colin Fleming, Eugénia Rodrigues and Graham Spinardi 12. The Use of Computerized Models in Different Policy Formulation Venues: The MARKAL Energy Model Paul Upham, Peter Taylor, David Christopherson and Will Mcdowall PART IV CONCLUSIONS AND NEW DIRECTIONS 13. The Tools of Policy Formulation: New Perspectives and New Challenges Andy J. Jordan, John R. Turnpenny and Tim Rayner Index